Herpes Simplex Virus 1 Coinfection Modifies Adeno-associated Virus Genome End Recombination - Meier, Anita Felicitas (J Virol, 2021)
Wild-type adeno-associated virus (AAV) can only replicate in the presence of helper factors, which can be provided by coinfecting helper viruses such as adenoviruses and herpesviruses. The AAV genome consists of a linear, single-stranded DNA (ssDNA), which is converted into different molecular structures within the host cell. Using high-throughput sequencing, we found that herpes simplex virus 1 (HSV-1) coinfection leads to a shift in the type of AAV genome end recombination. In particular, open-end inverted terminal repeat (ITR) recombination was enhanced, whereas open-closed ITR recombination was reduced in the presence of HSV-1. We demonstrate that the HSV-1 protein ICP8 plays an essential role in HSV-1-mediated interference with AAV genome end recombination, indicating that the previously described ICP8-driven mechanism of HSV-1 genome recombination may be underlying the observed changes. We also provide evidence that additional factors, such as products of true late genes, are involved. Although HSV-1 coinfection significantly changed the type of AAV genome end recombination, no significant change in the amount of circular AAV genomes was identified. IMPORTANCE Adeno-associated virus (AAV)-mediated gene therapy represents one of the most promising approaches for the treatment of genetic diseases. Currently, various GMP-compatible production methods can be applied to manufacture clinical-grade vector, including methods that employ helper factors derived from herpes simplex virus 1 (HSV-1). Yet, to date, we do not fully understand how HSV-1 interacts with AAV. We observed that HSV-1 modulates AAV genome ends similarly to the genome recombination events observed during HSV-1 replication and postulate that further improvements of the HSV-1 production platform may enhance packaging of the recombinant AAV particles.